The study of rheological and physical dough properties of the winter wheat varieties - N. S. Kravchenko; D. M. Marchenko; О. А. Nekrasova; Yu. N. Alty-Sadykh (Зерновое хозяйство России, 2021)
There have been represented the study results of flour quality of the winter bread wheat varieties of semi-intensive type of the FSBSI Agricultural Research Center “Donskoy”. The purpose of the current study was to estimate variability of the values of indicators that characterize physical and rheological dough properties, to identify the correlation between them, and to isolate genetic sources. The objects of study were 20 winter bread wheat varieties. Field trials were carried out in 2017–2019 in the fields of the department of winter wheat breeding and seed production, the forecrop was maize for grain. The variety ‘Don 107’ was used as a standard. The quality of grain and flour of the winter bread wheat varieties was assessed in the laboratory for biochemical estimation of breeding material and seed quality. There have been identified the varieties ‘Asket’ (26.9%), ‘Podarok Krymu’ (26.2%), ‘Zolotoy Kolos’ (25.5%) and ‘Izyuminka’ (25.5%) with the maximum gluten content in grain. It was determined that the trait ‘gluten deformation index’ varied from 62 u.v. to 77 u.v., all varieties corresponded to the 1st quality class. There have been identified the genotypes ‘Volny Don’, ‘Don 93’, ‘Premiera’, ‘Podarok Krymu’, ‘Ambar’, ‘Donskoy Surpriz’ and ‘Izyuminka’ with low values of the variation coefficient of the trait. There have been identified the varieties ‘Krasa Dona’ (6.7%), ‘Zhavoronok’ (6.8%) and ‘Asket’ (8.2%) with low values of the variation coefficient of the trait ‘specific work of dough deformation’. There have been identified the varieties ‘Don 93’, ‘Izyuminka’ and ‘Podarok Krymu’, which according to P/L corresponded to the class of strong wheat. It was found that the varieties ‘Zolotoy Kolos’ and ‘Volnitsa’ corresponded to the class of strong wheat according to the valorimetric assessment. Correlation analysis showed that the rheological dough properties were significantly influenced by gluten content in grain. There has been estimated the quantitative manifestation and variability of the traits, which characterize the rheological and physical dough properties. There have been identified the varieties with the smallest varietal variation of traits, which are recommended to use in the breeding process as sources of useful traits and properties. The selection according to the traits ‘delute of dough’ and ‘valorimetric assessment’ allow developing and introducing into production genotypes with good baking properties.